Water-Sediment Variation and Characteristics of Erosion and Deposition in Baihetan Reservoir Area - LUO Gang, XIAO Xiao, WU Di, JISHA Ri-fu, LU Jun (长江科学院院报)
[Objective] This study aims to investigate the dramatic changes in water-sediment processes within the Jinsha River reservoir area following the impoundment and operation of the Wudongde and Baihetan cascade hydropower stations. Using multi-source observational data, the study reveals the variation patterns of water and sediment fluxes between the two dams, the spatiotemporal distribution characteristics of riverbed erosion and deposition, and their driving mechanisms. The findings provide scientific support for reservoir safety operation, navigation channel management, and ecological conservation. [Methods] The study was conducted using runoff-sediment transport data from 2015 to 2023 at the Wudongde and Baihetan hydrological stations, fixed cross-sectional topographic surveys from 2016 to 2023, and hydrodynamic measurements collected downstream of the Wudongde Dam in 2023. Water-sediment relationship analysis was employed to examine the response patterns between runoff and sediment transport. Erosion and deposition volumes were calculated using the cross-sectional method, with 825 m water level as the reference and the channel storage volume estimated via the frustum formula. Spatial variations of erosion and deposition were quantified by overlaying thalweg line and comparing morphological changes of typical cross-sections (JC199, JC153, JC126). [Results] 1) Water-sediment flux variations: Annual runoff exhibited a slight decrease, 2% at the Wudongde station and 17.8% at the Baihetan station. Annual sediment transport plummeted by more than 90%, primarily due to the “cumulative sediment retention effect” of upstream reservoirs. Intra-annual runoff distribution demonstrated a “peak-shaving and valley-filling” pattern, with a 22%-48% increase in December and a 16%-38% decrease in July. Sediment transport was concentrated from June to October (accounting for over 63%), yet monthly averages dropped by more than 95%. A progressive downstream sedimentation trend was observed in September. 2) Spatiotemporal evolution of erosion and deposition: erosion dominated during dry season (October-May), while deposition dominated the wet season (May-October). From 2021 to 2023, a net deposition volume reached 12.63 million m3, showing an overall cumulative trend. Spatially, a strong erosion zone formed at the reservoir tail driven by the high-kinetic-energy discharges from the Wudongde Dam. The core deposition area in the main reservoir was found 25-75 km upstream of the dam. In the tributary-affected zone, the Heishui River confluence showed prominent deposition. 3) Driving mechanisms of erosion and deposition: In terms of hydrodynamic forces, erosion was triggered by high flow velocities and strong sediment-carrying capacities within 20 km downstream of the Wudongde Dam, while beyond this zone, deposition was promoted by slower flows and weaker sediment-carrying capacities. Regarding tributary replenishment, tributaries such as the Pudu River, Xiaojiang River, and Heishui River contributed an average annual sediment transport of 5.73 million tons (2011-2022), accounting for over 46% of the deposition volume in the reservoir area. [Conclusions] The operation of cascade hydropower stations has restructured the water-sediment process. Although the runoff volume decreased slightly, its intra-annual redistribution was significant, and the sediment transport plummeted by 96% due to the “cumulative sediment retention effect”, with sediment being concentrated in flood season. The erosion and deposition in the reservoir area exhibit a spatial pattern of “erosion at the tail and deposition in the head”. The reservoir tail is eroded by the discharged flow, while the main reservoir experiences deposition due to reduced flow velocity and tributary replenishment, with the confluence of the Heishui River being a key source of deposition. A clear long-term deposition trend is observed, and it is necessary to focus on the high-risk deposition zone 25-75 km upstream of the dam and the sections with drastic morphological changes at tributary estuaries. These findings provide a quantitative basis for the joint operation of cascade reservoirs, navigation channel maintenance, and sediment management.